Prefabricated Acrylic Cap Splint: A Minimally Invasive and Conservative Intervention for Paediatric Mandibular Fractures: A Case Report - Nishima; Anil Gupta; Shalini Garg; Vishal Sharma; Sugandha Sharma (Journal of Clinical and Diagnostic Research, 2023)
Dental traumatic injuries in paediatric patients result in a painful experience for both the parents and the child. Although children may exhibit similar fracture patterns as seen in adult traumatic injuries, there are various factors to consider when treating fractures in paediatric patients, which pose challenges for paediatric dentists. There are numerous treatment options available for managing maxillofacial fractures, such as open reduction, closed reduction, immobilisation with open or closed cap splint, with or without circummandibular wiring, and the use of mini plates, among others. In this present case report, a five-year-old child presented with multiple step deformities in the mandible. Since the patient had deciduous dentition, the main concerns were the high possibility of disruption to the periosteal envelope, which could affect the growth of the mandibular processes, and damage to developing permanent tooth buds. These were key considerations when planning the appropriate treatment. Taking into account these potential complications associated with other invasive procedures, a minimally invasive conservative management approach was chosen for the child, which proved to be highly successful and cost-effective. Undisplaced fractures in paediatric patients should always be treated or stabilised using the closed reduction method.